Differentiation of spermatogonial stem cells by soft agar three-dimensional culture system. Issue 1 (4th December 2019) - Mohammadzadeh, Elham; Mirzapour, Tooba; Nowroozi, Mohammad Reza; Nazarian, Hamid; Piryaei, Abbas; Alipour, Fatemeh; Modarres Mousavi, Sayed Mostafa; Ghaffari Novin, Marefat
Abstract: Since proliferation and differentiation of spermatogonial stem cells (SSCs) in culture system provide successful transplantation in this study, culture of human SSCs was compared to SACS (soft agar culture system), gelatin and control groups. The cells were isolated from seminiferous tubules of non-azoospermia patients (NOA) and cultured in DMEM for 3 weeks. The presence of SSCs in culture system was confirmed by immunocytochemistry of GFR-α1 and ITGα6 antibodies. The proliferated cells were cultured in three mentioned groups in the presence of retinoic acid and Sertoli cells conditioned medium for another 2 weeks. The number of colonies in the SACS group was significantly higher than two other groups. Before 2 weeks of culture, only Oct4 expression was observed in testicular cells (2.32 ± 0.25). After 2 weeks, the expression of Oct4 in the gelatin group was higher than that of the SACS group on day 7. The maximum expression of Stra8 was observed in SACS and gelatin groups after 7 days, but its expression was significantly decreased after 14 days of culture ( p < .05). The expression of Scp3 and Acrosin genes were higher after 14 days in the SACS group compared to other groups. SACS has positive effects on proliferation and differentiation of hSSCs.